Enhanced triplet-triplet annihilation in bicomponent organic systems by using a gap plasmon resonator - Park, Jun Kue; Lee, Gi Yong; Jung, Kinam; Ko, Doo-Hyun; Han, Il Ki; Ko, Hyungduk (ROYAL SOC CHEMISTRY, 2015)
The triplet-triplet annihilation (TTA) efficiency in bicomponent organic systems is investigated by employing a gap plasmon resonator. In our structure, strong absorption peaks arising from coupling between localized surface plasmons and surface plasmon polaritons closely overlap the Q band of porphyrin, leading to higher triplet concentrations within the film. We find that at ultra-low excitation intensities on the order of watts per square centimeter (W cm(-2)), TTA becomes predominant for the organic system on a gap plasmon resonator. A strong surface-enhanced Raman scattering intensity is observed in this substrate, verifying the near-field enhancement.
Keywords: PHOTON UP-CONVERSION; RAMAN-SCATTERING; SURFACE; POLARITONS; PORPHYRIN; NANOSTRUCTURES; FLUORESCENCE; EXCITATION; SPECTRA; ARRAY